Contribution to the knowledge of the Nolini of the Maputo Special Reserve in South Mozambique with description of two new species and several taxonomic updates (Lepidoptera, Nolidae, Nolinae) - László, Gyula M.; Vetina, Alvaro A. (Zootaxa, 2019)
Present paper contains the first comprehensive summary of the Nolini species of the Maputo Special Reserve collected between November 2016 and February 2018. The Nolini fauna counts 21 species in total, 17 species are proved to be new for the fauna of Mozambique, two species are new to science and described here as Mecothrix maputuana sp. n. and Meganola shangaana sp. n. The subgenus Mecothrix Hacker, 2012 is upgraded to genus rank. Mecothrix cana Hacker, 2012 and Nola submelanoscelis Hacker, 2012 are downgraded to subspecies rank (Mecothrix aegyptiaca cana Hacker, 2012 stat. n., Nola biangulata submelanoscelis Hacker, 2012 stat. n.). Meganola meridianissima Hacker, 2012 syn. n. and Meganola kakamega Hacker, 2012 syn. n. are synonymized with Meganola bispermutata Hacker, 2012, in addition Nolidia nanoxantha Hacker, 2012 syn. n. and Nolidia polionana Hacker, 2012 syn. n. are synonymised with Nolidia elachistomorpha Hacker, 2012. Nolidia elachistomorpha is transferred to the genus Hampsonola László, Ronkay & Ronkay, 2015 (Hampsonola elachistomorpha (Hacker, 2012) comb. n.). With 43 colour and 40 black and white figures.